Earth : an introduction to physical geology - Tarbuck, Edward J.; Lutgens, Frederick K. (Upper Saddle River, N.J. : Prentice Hall, 1999)
An introduction to physical geology that explains how the Earth works; includes a CD-ROM with animations, interactive activities, and enhanced text art designed to reinforce key geological concepts.
Includes index.
Title on computer disc: GEODe II.
Adult
System requirements for accompanying computer disc: IBM compatible 386 or faster ; 4MB RAM (8MB suggested) ; Windows 3.1 (enhanced mode) or Windows 95 ; SVGA (256 colors in 640x480) ; double-speed CD-ROM drive.
System requirements for accompanying computer disc: Macintosh ; 4MB of free RAM ; System 6.0.7 or higher ; 13" or larger 256 color display (640x480 or higher) ; double-speed CD-ROM drive.
Keywords: Physical geology; Geology